Analisis Karakteristik Fisik dan Meteorologi DAS Bengkulu - Gita Ivana Suci Lestari Faski (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2021)
Bengkulu watershed experiences flooding at least two times a year during the rainy season. The flood is one of the hydrometeorological disasters influenced by the physical and meteorological characteristics of the watershed. The characteristics are the basis for planning and management in the watershed. Therefore, this study aims to analyze the physical characteristics and meteorological characteristics of the Bengkulu watershed, as a basis for planning and managing the watershed, to minimize the incidence and impact of hydrometeorological disasters in the watershed. The method used in this research is a quantitative descriptive method of the physical and meteorological characteristics of the Bengkulu watershed. The physical characteristics of the watershed that were analyzed were morphometry, topography, soil type, and land use in the Bengkulu watershed. While the meteorological characteristics analyzed were rainfall and air temperature in the Bengkulu watershed. The results show that the physical characteristics of the Bengkulu watershed have a low capacity to store water, so that the infiltration is small, but the runoff rate is small and the flow type is moderate. However, runoff tends to increase. This is due to decreasing changes in forest land use, supported by increasing rainfall, and small variations in air temperature.